Making the world safe for workers : labor, the Left, and Wilsonian internationalism - McKillen, Elizabeth, 1957- (Working class in American history., 2013)
In this intellectually ambitious study, Elizabeth McKillen explores the significance of Wilsonian internationalism for workers and the influence of American labour in both shaping and undermining the foreign policies and war mobilization efforts of Woodrow Wilson's administration. McKillen highlights the major fault lines and conflicts that emerged within labor circles as Wilson pursued his agenda in the context of Mexican and European revolutions, World War I, and the Versailles Peace Conference.